2004
DOI: 10.1557/jmr.2004.0265
|View full text |Cite
|
Sign up to set email alerts
|

Influence of distributed trap states on the characteristics of top and bottom contact organic field-effect transistors

Abstract: Numerical simulations of organic field-effect transistors (OFET) of bottom and top contact (BOC, TOC) design with different source/drain contacts were carried out considering an exponential distribution of trap states in the gap of the active layer (a-Si model). For ohmic contacts, the current-voltage characteristics are similar to the trap-free case and there is not much difference between the two designs. However, the currents are lower due to immobile trapped charges, the threshold voltage is shifted, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…For the temperature dependency of parameters in a device, more complicated models such as variable-range hopping are preferred [12]. The experimental results support well the application of the trapping model for dc analysis of organic devices at a constant temperature [13,14]. In the present work, we have used the MTR model to analyze a device behavior at constant temperature assuming that the semiconductor has an amorphous structure with different distribution of localized states (a polymer film).…”
Section: Drain Current and Subthreshold Swingsupporting
confidence: 60%
“…For the temperature dependency of parameters in a device, more complicated models such as variable-range hopping are preferred [12]. The experimental results support well the application of the trapping model for dc analysis of organic devices at a constant temperature [13,14]. In the present work, we have used the MTR model to analyze a device behavior at constant temperature assuming that the semiconductor has an amorphous structure with different distribution of localized states (a polymer film).…”
Section: Drain Current and Subthreshold Swingsupporting
confidence: 60%
“…[94] Device modeling has been used to understand the subthreshold characteristics of OFETs. [95] Based on an analysis of the relationship between the current decay at the early stages after FET turn-on and the hole concentration in the channel, Street et al have suggested that charge trapping occurs due to formation of low-mobility bipolarons by reaction of two polarons. [93,96] However, Deng et al…”
Section: Degradation Mechanisms Causing Thresholdvoltage Instabilitiesmentioning
confidence: 99%
“…This is much easier than calculation using simulators, 19,64,65 In the DBTTF transistors (Fig. 4), the onset voltage V on is shifted by 15, 35, and 80 V for PS, HMDS, and bare transistors, respectively.…”
Section: Simulationmentioning
confidence: 99%